Meningkatkan motivasi belajar siswa pada pembelajaran IPS menggunakan model pembelajaran kooperatif tipe group investigation - Nur Laila; Hariyono Hariyono; Sumarmi Sumarmi (Universitas Negeri Malang, 2016)
This study aims to increase students' motivation in learning Social Sciences through the implementation of cooperative learning model Group Investigation. The method used in this research is the Classroom Action Research are implemented in the first cycle and the second cycle. Each cycle consists of five convened four meetings in the classroom one meeting outside of instructional hours. The type of action taken is learning social studies using cooperative learning model type Group Investigation. Results of research conducted showed an increase in student motivation in the first cycle the percentage reached 77% criterion of